The autobiography of Miss Jane Pittman [videorecording (DVD)] - Korty, John; Tyson, Cicely; Chaney, Barbara; Dysart, Richard; Helmond, Katherine; Murphy, Michael, 1938-; Odetta, 1930-2008; Gaines, Ernest J., 1933- (Classic Media, Inc. ; Sony Wonder, 2005)
The history of blacks in the South as seen through the eyes of a 110-year-old former slave. Based on the novel by Ernest J. Gaines.